Principal and Teacher Strategies in Improving the Quality of Independent Curriculum-Based Learning - Maharani, Nafikha Putri Arthamevia; Purba, Yesica Mai Tuwanti Br; Riska, Eva Annisa; Andika, Lingga Dwi; Laksono, Anton April; Oktaviani, Fitriana (Jurnal Inovasi Pembelajaran Karakter, 2025)
Improving the quality of education in Indonesia is a national priority, along with implementing the Merdeka Curriculum, which demands school innovation. This qualitative study describes the Principal's strategy through interviews, observations, and document studies. The results show three main strategies: strengthening human resources through training, learning strategies that include planning learning outcomes and character development, and building effective communication with teachers, parents, and the community. This study highlights the crucial role of the Principal in creating an adaptive and collaborative learning environment. It provides guidance for improving the quality of education and government policies related to the Merdeka Curriculum. The novelty of this study lies in the comprehensive description of the Principal's strategy, which includes strengthening human resources, learning innovation, and effective collaboration. The results of this study are helpful for the community because they can guide principals in improving the quality of education in their respective schools.